Pengaruh Sikap Keuangan, Literasi Keuangan, Dan Gaya Hidup Terhadap Pengelolaan Keuangan Mahasiswa Ntt Di Yogyakarta - Matan Langoday, Agustinus Petrus; Mulida, Alfiatual; Kusumawardhani, Ratih (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of financial attitude, financial literacy, and lifestyle on the financial management of NTT students studying in Yogyakarta. The research aims to analyze the partial effects of these variables on students’ financial management. A quantitative approach with a descriptive design was employed. Data were collected from 100 respondents using questionnaires and analyzed through multiple linear regression. The results indicate that financial attitude, financial literacy, and lifestyle have a positive and significant effect on financial management. The findings imply that strengthening financial knowledge and fostering positive financial attitudes can improve students’ financial management behavior.